2019
DOI: 10.25518/1780-4507.18199
|View full text |Cite
|
Sign up to set email alerts
|

Tolérance au déficit hydrique de cinq espèces prioritaires pour le reboisement au Burkina Faso

Abstract: Description du sujet. Dans les régions arides et semi-arides, la disponibilité en eau est l’un des facteurs limitant de la croissance et du développement des arbres. L’étude de la réponse au déficit hydrique des espèces végétales permettrait de sélectionner du matériel végétal résistant pouvant se développer dans les zones sujettes à des déficits hydriques périodiques. Objectifs. L’objectif est d’évaluer la tolérance au stress hydrique de cinq espèces prioritaires pour le reboisement que sont Faidherbia albid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Cela montre la grande résistance des cellules de C. adscendens à une perte d'eau. Selon Kagambèga et al (2019), l'évaluation de la teneur en eau des tissus constitue un paramètre de référence de la prédiction du déficit hydrique qui s'exprime par les pertes de turgescence de tissus végétaux. Cette stratégie regroupe l'ensemble des mécanismes qui permettent à la plante de maintenir un potentiel hydrique plus élevé en évitant la déshydratation des tissus et le maintien de son métabolisme cellulaire.…”
Section: Pression Osmotiqueunclassified
“…Cela montre la grande résistance des cellules de C. adscendens à une perte d'eau. Selon Kagambèga et al (2019), l'évaluation de la teneur en eau des tissus constitue un paramètre de référence de la prédiction du déficit hydrique qui s'exprime par les pertes de turgescence de tissus végétaux. Cette stratégie regroupe l'ensemble des mécanismes qui permettent à la plante de maintenir un potentiel hydrique plus élevé en évitant la déshydratation des tissus et le maintien de son métabolisme cellulaire.…”
Section: Pression Osmotiqueunclassified
“…When plants were in a vegetative state (50 days after planting), above-ground plant materials were cut at soil level and above-ground dry biomass of the plants was determined after drying in an oven at 65°C for 72 h using a precision balance (0.01g). These parameters provide a better understanding of the mechanism adopted by each species under conditions of water deficit combined with competition and thus help to evaluate species adaptation potential (Kagambèga et al 2019).…”
Section: Measured Parametersmentioning
confidence: 99%
“…To characterize and compare the degrees of tolerance of the different species to water deficit, the stress sensitivity index (SSI) was calculated at the end of the experiment following the different regimes. In this study, the stress sensitivity index developed by Fischer and Maurer (1978) was used because it is successfully applied in many studies (Nana et al 2009;Kagambèga et al 2019) and was determined from the height of the plant species using the formula below:…”
Section: Sensitivity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms our results for certain genotypes such as V16, V22, V28, V8 and V19 which presented a small number of pods and a low biomass (Figure 1). In fact, the results of [23] on the analysis of the tolerance to water deficit of five different species indicated that the morpho-physiological parameters of plants were negatively affected by water restriction, except some species such as Acacia senegal which have shown their performance due to their low sensitivity to water stress. The most tolerants varieties in our study are V2, V7, V9, V24, V32, V35 and V36 (Figure 1).…”
Section: Comparison Of Some Growth Parametersmentioning
confidence: 99%